Hydraulic Properties of Flow over Vertical Drop Weir - เทพวงษ์ รณกร; โรจนเมฆา สุธรรม; สุขจินดา พิทยา; ไทยยืนวงษ์ สันติ (Rattanakosin Journal of Science and Technology, 2021)
The objective of this research was to test the hydraulic properties of the flow through the standing wall hemispherical ridge. The flow through the open channel was tested in a hydraulics laboratory. Weirs were 75 mm wide and 70, 100 and 150 mm high, and the weir crest thickness was 18, 25, 40 and 55 mm. From the study, it was found that at the same flow rate, the height of the water above the weir crest increased when the weir is thicker. When calculating the flow coefficient compared to the thickness of weir, it was found that the smaller weirs have a flow coefficient closer to 1 than the thicker weirs.